Notes on the Guidelines of the 2009 Online Workshop on Theories of Consciousness - Júnior, Alfredo Pereira (Scripta, 2022)
The Online Workshop on Theories of Consciousness (OWTC), a set of live online (text only) discussions carried in 2009 at the site Nature.com, was an attempt to organize and find minimal agreement on the epistemological bases for the scientific and philosophical research on the Theory of Consciousness. This paper covers the guidelines I proposed to the group, some issues discussed after the presentation of the first seminars on "Models of Conscousness", by Anil Seth, "Cognitive Theories of Consciousness", by Vincent de Gardelle, and some discussions with the participants about these topics. Following the Concluding Remarks, I added an Epilogue written some years after the Workshop.